Islam today: short introduction to the muslim World - "Ahmed, Akbar.S." (London, 2001)
This lively and compelling book sets out to bridge the gulf of misunderstanding. Islam, argues Akbar Ahmed, does not mean the subordination of women, contempt for other religions, opposition to the modern world, or barbaric punishments for petty crimes. One cannot fully come to terms with modern Islam without understanding its sources and traditions.
Keywords: Islam